Safety and Quality Improvement of NaCl-Reduced Banana and Apple Fermented with Lacticaseibacillus paracasei - Jose M. Martín-Miguélez; Josué Delgado; Irene Martín; Alberto González-Mohino; Lary Souza Olegario (Foods)
Food preservation techniques changed during the industrial revolution, as safer techniques were developed and democratized. However, one of the simplest techniques, adding salt, is still employed in a wide variety of products, not only as a flavor enhancer but as a method to allow for the controlled fermentation of products such as fruits. The objective of the present study consists of evaluating the quality of different salt-reduced fermented fruits through the application of the lactic acid bacteria (LAB) Lacticaseibacillus paracasei and vacuum, as well as assessing the LAB as a preventive measure against Escherichia coli O157:H7. To achieve this goal, microbial plate count techniques, the evaluation of the physicochemical characteristics, and Check-All-That-Apply/Rate-All-That-Apply sensory analyses were performed on bananas and apples individually fermented at 30 °C for 2 and 7 days, respectively. Additionally, a challenge test using E. coli as pathogenic bacteria was performed. The characteristics of each fruit determined the efficiency of the LAB’s protective activity. LAB-inoculated batches controlled the growth of E. coli in both salted fruits, but this pathogenic bacterium in the apple case was controlled even in the salt-reduced batch. Sensorially, only inoculated fermented apples found a reduction in off-flavor and old fruit smell; however, higher acceptability was found in the salt-reduced with LAB batches of both fruits. Thus, Lacticaseibacillus paracasei proved to be a cheap, easy, and feasible protective method that can ensure a protective strategy on salt-reduced fermented apples and should be studied particularly for different fruits.